Glycaemic profile in the second and third trimesters of normal pregnancy compared to non-pregnant adult females. (March 2020) - Nigam, Aruna; Varun, Neha; Sharma, Sumedha; Munjal, YP; Prakash, Anupam
Aim: To assess the glycaemic profile and glycaemic variation in the second and third trimesters of normal pregnancies. Methodology: Healthy pregnant women aged 19–35 years between 24 and 36 weeks of gestation were recruited for ambulatory glucose profile monitoring. A total of 18 women in the second trimester, 15 women in the third trimester and 9 healthy non-pregnant women were recruited providing, respectively, 205 days (19, 680 data points), 147 days (14, 112 data points) and 100 days (9, 600 data points) for analysis. Results: Mean blood glucose level was 20.2% lower in the second trimester and 10.6% lower in the third trimester than non-pregnant women (p < 0.001). In pregnancy, it took 15 to 20 minutes more to reach peak postprandial blood glucose levels compared to non-pregnant women (p = 0.003). Glycaemic variability was more in the third trimester (p < 0.001). Conclusion: There is tight blood sugar control along with lower mean blood glucose in healthy pregnant women compared to non-pregnant women. Despite this tight glycaemic control, glycaemic variability is higher during pregnancy.